Differences in Physical Fitness Levels of Students 01 Enam Lingkung and 07 Sintoga Elementary School Students - Saputra, Tomi; Asmi, Ali; Nur, Hasriwandi (Yayasan Sekora, 2017)
This research originated from the author's desire to know about the level of physical fitness of the students of SD Negeri 01 Enam Lingkung with SD Negeri 07 Sintoga, Padang Pariaman Regency. The purpose of this study was to get a real picture of how the level of physical fitness of each school student and at the same time to see the comparison of the physical fitness level of students of SD Negeri 01 Enam Lingkung with SD Negeri 07 Sintoga, Padang Pariaman Regency. This type of research is Ex Post Facto. The population was all students of SD Negeri 01 Enam Lingkung with SD Negeri 07 Sintoga, Padang Pariaman Regency, which amounted to 375 students. The sample was taken by purposive sampling technique, thus the number of samples was 63 male students. Data were analyzed using the T-test data analysis technique. From the results of the data analysis, it shows that there are differences in the physical fitness level of male students in SD Negeri 01 Enam Lingkung and SD Negeri 07 Sintoga, it is obtained tcount = 3.57 and ttable = 1.00. And the physical fitness level of SD Negeri 07 Sintoga students was better, because it was found that the mean (average value) of SD Negeri 07 students was 10.97 greater than the mean (average value) of students at SD Negeri 01 Enam Lingkung which was 10